Emergency groin hernia: outcome after mesh and non‐mesh repair. Issue 1 (21st December 2022) - Kumar, Dileep; Wu, Diana; Tan, Brandon; Guilbert, Michael; Muthukumarsamy, Girivasan
Abstract: Background: Emergency inguinal and femoral hernia repair can be done by suture or mesh repair, there is still scepticism around using mesh. We aim to evaluate the usage of mesh and the outcome of emergency groin hernia repair after mesh and suture repair. Methods: Retrospective cohort study of adult patients who underwent emergency inguinal and femoral hernia repair from 1st January 2018 to 31st July 2020. Electronic data and case notes were reviewed and outcome data were collected. Results: Eighty‐nine emergency groin hernia repairs were carried out. Sixty‐two were males, 60 inguinal hernia and 29 femoral hernia. Median age was 72 years (range 20–95). 74 (83.1%) were primary hernia and 15 (16.9%) recurrent hernias. 67 (75.3%) mesh and 22 (24.7%) suture repairs were carried out. Eleven cases required bowel resection and of those 10 had suture repair. Inguinal hernia was more likely to have mesh repair as compared to femoral ( P ‐value 0.002). Median length of stay was significantly lower in mesh group 2 days (1–5 IQR) versus 7.5 days (5–11 IQR) in suture repair group ( P ‐value <0.0001). Five cases (6.74%) had wound complications (3 wound infections, 2 haematoma). With median 20 months (range 6–36 months) follow‐up, 1 recurrence each in both mesh and suture repair groups, no mesh infection and 2 (2.2%) 30‐day mortality recorded. Wound infection, recurrence and reoperation were not statistically different in two groups. Conclusion: Emergency groin hernia are amenable to mesh repair and in case of bowel resection or gross contamination non‐ mesh repair is recommended. Abstract : Emergency groin hernia are amenable to mesh repair and in case of bowel resection or gross contamination non‐ mesh repair is recommended. In this retrospective cohort study, we aim to evaluate the usage of mesh and the outcome of emergency groin hernia repair after mesh and suture repair. We conclude that emergency groin hernia is amenable to mesh repair and in case of bowel resection or gross contamination non‐mesh repair is recommended.